Evaluation of Cocoa Agribusiness in South Manokwari Regency, West Papua, Indonesia - Junita Br. Nambela; Aser Rouw; Surianto Sipi (Indonesian Coffee and Cocoa Research Institute, 2020)
South Manokwari has triumphed with cocoa since 1980 but that glory has faded in recent years. Recently, this regency is faced with various problems for the development of cocoa agribusiness. The purpose of the study was to evaluate the current cocoa-based business in South Manokwari. This research was conductedin three districts in South Manokwari namely Oransbari, Ransiki, and Momi Waren. The study was conducted using the purposive random sampling technique on 119 respondents. The distribution of respondents in the three districts was: Oransbari 44 respondents; Ransiki 42 respondents; and Momi Waren 33 respondents. Basedon the study results, it was known that the average plantation ownership by the farmers was 1.09 ha. Ninety nine percent of farmers were still in productive age (15-65 years). The level of education was still low with 67.13% of farmers had no formal education or did not finish elementary school. Cultivation practices thatmust be improved included pruning (74.71%), fertilization (95.89%), pest and disease control (55.16%), and waste utilization (82.07%). The cocoa beans’ average production was in the range of 71.67–173.33 kg dry beans or 21.67–1000 kg fresh beans per ha harvested from 1,574 ha of farmers’ cocoa land in South Manokwari. Meanwhile, the average prices for cocoa beans were USD 0.24–USD 0.36/kg for the fresh beans and USD 1.20–USD 2.23/kg for the dried beans.